1998
DOI: 10.1016/s0022-5347(01)63944-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Testosterone on Prostate Volume, Serum and Semen Prostate Specific Antigen Levels in Healthy Young Men

Abstract: Despite significant elevations in serum total and free testosterone, healthy young men do not demonstrate increased serum or semen PSA levels, or increased prostate volume in response to exogenous testosterone injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 20 publications
5
56
0
4
Order By: Relevance
“…One alternative explanation for the decreased PSA concentration seen in the obese men may be a decrease in circulating levels of androgens that are more likely to be found in obese men (13). However, previous studies have shown that only for hypogonadal men, who underwent testosterone replacement treatment, PSA levels increases (14). Although for healthy young men suffering testosterone administration, PSA did not change (15).…”
Section: Discussionmentioning
confidence: 93%
“…One alternative explanation for the decreased PSA concentration seen in the obese men may be a decrease in circulating levels of androgens that are more likely to be found in obese men (13). However, previous studies have shown that only for hypogonadal men, who underwent testosterone replacement treatment, PSA levels increases (14). Although for healthy young men suffering testosterone administration, PSA did not change (15).…”
Section: Discussionmentioning
confidence: 93%
“…Literature also offers studies that tried to assess the correlation in the other way. Cooper et al administered Testosterone in 31 subjects and monitored the prostate volume and PSA levels but despite significant elevations in serum total and free Testosterone, healthy young men did not demonstrate increased serum or semen PSA levels, or increased prostate volume [6]. Based on a study of 65 men Gustafsson et al also observed that there was no relationship between PSA and Testosterone [7].…”
Section: Discussionmentioning
confidence: 99%
“…Хотя снижение концентраций те-стостерона сыворотки до диапазона, соответствующего определению кастрации, явно вызывает регрессию рака предстательной железы и снижает уровни простато-специфического антигена, имеющиеся доказательные данные говорят об ограниченной способности андро-генов стимулировать рост рака предстательной железы, поскольку максимальная андрогенная стимуляция до-стигается на низких концентрациях тестостерона [6]. Например, воздействие супрафизиологических уров-ней тестостерона на протяжении до 9 месяцев не при-вело к увеличению уровней простатоспецифического антигена или объема предстательной железы у здоро-вых добровольцев [68]. Наличие конечного предела у способности андрогенов стимулировать рост пред-стательной железы обозначается термином «модель насыщения» [69,70].…”
Section: заявление 8 существующие доказательные данные не подтверждаunclassified